2019
DOI: 10.5194/wes-4-407-2019
|View full text |Cite
|
Sign up to set email alerts
|

Detection of wakes in the inflow of turbines using nacelle lidars

Abstract: Abstract. Nacelle-mounted lidar systems offer the possibility of remotely sensing the inflow of wind turbines. Due to the limitation of line-of-sight measurements and the limited number of focus positions, assumptions are necessary to derive useful inflow characteristics. Typically, horizontally homogeneous inflow is assumed which is well satisfied in flat, homogeneous terrain and over sufficiently large time averages. However, it is violated if a wake impinges the field of view of one of the beams. In such si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…From the results presented in part 3.1, it is shown that the wind regimes in neutral and unstable boundary layers have large difference even under the same low surface roughness length z 0 = 0.001 m. Under the effect of surface temperature flux, the convective boundary layer forms a wind regime with less shear and higher turbulence intensity compared with that in neutral condition, leading to the larger Reynolds stress and thus faster velocity recovery in the wind turbine wake flow. The real-time preview control strategy needs the accurate capture of the dynamic wake characteristics to reconstruct to a certain extent the inhomogeneous inflow field of every wind turbine [66,67]. The wake flow structure corresponding to the meandering or larger scale is the most important information and feasible to model [65].…”
Section: Discussionmentioning
confidence: 99%
“…From the results presented in part 3.1, it is shown that the wind regimes in neutral and unstable boundary layers have large difference even under the same low surface roughness length z 0 = 0.001 m. Under the effect of surface temperature flux, the convective boundary layer forms a wind regime with less shear and higher turbulence intensity compared with that in neutral condition, leading to the larger Reynolds stress and thus faster velocity recovery in the wind turbine wake flow. The real-time preview control strategy needs the accurate capture of the dynamic wake characteristics to reconstruct to a certain extent the inhomogeneous inflow field of every wind turbine [66,67]. The wake flow structure corresponding to the meandering or larger scale is the most important information and feasible to model [65].…”
Section: Discussionmentioning
confidence: 99%
“…blades, shaft, tower) are represented by a number of bodies, which are defined as an assembly of Timoshenko beam elements (Larsen et al, 2013). The aerodynamic part of the code is based on the blade element momentum (BEM) theory, extended to handle dynamic inflow and dynamic stall (Hansen et al, 2004), among others. Top and front views of the CW lidar (a, b) and PL lidar (c, d) scanning patterns shown by the blue dots.…”
Section: Methodsmentioning
confidence: 99%
“…The algorithm relies on 10-min statistics of the lidar measurements and follows the approach of Held and Mann (2019). The idea is to detect the increase in turbulence originating from wakes with respect to the free wind conditions.…”
Section: Wake Detection Algorithmmentioning
confidence: 99%
“…We select a log-normal and normal pdf for T I and measurements at several ranges are omitted in the present work. Improved wake detection can be obtained by establishing thresholds conditional to the ambient wind conditions (i.e., wind speed, turbulence and atmospheric stability) and by assessing the detection parameters for shorter time periods (Held and Mann, 2019). More detailed detection algorithms including wake dynamic characteristics are proposed in the literature .…”
Section: Wake Detection Algorithmmentioning
confidence: 99%
See 1 more Smart Citation